High-Density of FcγRIIIA+ (CD16+) Tumor-Associated Neutrophils in Metastases Improves the Therapeutic Response of Cetuximab in Metastatic Colorectal Cancer Patients, Independently of the HLA-E/CD94-NKG2A Axis - Denis Musquer, Marie; Jouand, Nicolas; Pere, Morgane; Lamer, Juliette Eugène; Bézieau, Stéphane; Matysiak, Tamara; Faroux, Roger; Caroli Bosc, François-Xavier; Rousselet, Marie-Christine; Leclair, François; Mosnier, Jean-François; Toquet, Claire; et al. (Frontiers in Oncology, 2021)
Antibody-dependent cellular cytotoxicity (ADCC) in the anti-tumor effect of cetuximab in metastatic colorectal cancer (mCRC) is only based on the impact of FcγRIIIA (CD16) polymorphisms as predictive of therapeutic response. However, nature, density and therapeutic impact of CD16+ effector cells in tumor remain under documented. Moreover, the inhibition of cetuximab-mediated ADCC induced by NK cells by the engagement of the new inhibitory CD94-NKG2A immune checkpoint has been demonstrated in vitro only. This multicentric study aimed to determine in a cohort of mCRC patients treated with cetuximab, with both primary and paired metastatic available tumor tissues, 1) the nature and the density of CD16+ immune cells, 2) the expression profile of HLA-E/β2m by tumor cells as well as the density of CD94+ immune cells and 3) their impact on both objective response to cetuximab and survival. We demonstrated that CD16+ intraepithelial immune cells mainly correspond to tumor-associated neutrophils (TAN), and their high density in metastases was significantly associated with a better response to cetuximab, independently of the expression of the CD94/NKG2A inhibitory immune checkpoint. However, HLA-E/β2m, preferentially overexpressed in metastases compared with primary tumors and associated with CD94+ tumor infiltrating lymphocytes (TILs) was responsible for a poor overall survival. Altogether, these results strongly support the use of bispecific antibodies directed against both EGFR and CD16 in mCRC patients, to boost cetuximab-mediated ADCC in RAS wild-type mCRC patients. The preferential overexpression of HLA-E/β2m in metastases, associated with CD94+ TILs and responsible for a poor prognosis, provides convincing arguments to inhibit this new immune checkpoint with monalizumab, a humanized anti-NKG2A antibody, in combination with anti-CD16/EGFR bispecific antibody as a promising therapeutic perspective in RAS wild-type mCRC patients.